Data collection for sexually transmitted disease diagnoses: a comparison of self-report, medical record reviews, and state health department reports. - Niccolai, Linda M; Kershaw, Trace S; Lewis, Jessica B; Cicchetti, Domenic V; Ethier, Kathleen A; Ickovics, Jeannette R (Annals of epidemiology, 2005)
To compare three methods of data collection on case ascertainment of past chlamydia or gonorrhea diagnoses.
Keywords: Adolescent; Adult; Chlamydia Infections; Data Collection; Data Interpretation, Statistical; Disease Notification; Female; Gonorrhea; Humans; Interviews as Topic; Medical Records; Pregnancy; Prevalence; Public Health Informatics; Risk Factors; Self Disclosure; Sexually Transmitted Diseases; State Government; United States